2014
DOI: 10.1371/journal.pone.0093337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity and Nutrient Addition on Mangrove Excoecaria agallocha

Abstract: Effects of salinity on seed germination and growth of young (1 month old) and old (2-year old) seedlings of Excoecaria agallocha were investigated. Combined effects of salinity and nutrient level were also examined on old seedlings. Seed germination was best at 0 and 5 psu salinity. 15 psu salinity significantly delayed root initiation and decreased final establishment rate. All seeds failed to establish at 25 psu salinity. Young seedlings performed best at 0 and 5 psu, but growth was stunned at 15 psu, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 72 publications
2
46
0
Order By: Relevance
“…Reduced leaf production, decreased specific leaf area and increased leaf senescence with increased salinity is in accordance with the findings of Ball & Pidsley (1995) and Chen & Ye (2014). Leaf area reduction is considered to be the immediate response to salt stress (Parida & Das 2005, Reef & Lovelock 2015.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 86%
See 2 more Smart Citations
“…Reduced leaf production, decreased specific leaf area and increased leaf senescence with increased salinity is in accordance with the findings of Ball & Pidsley (1995) and Chen & Ye (2014). Leaf area reduction is considered to be the immediate response to salt stress (Parida & Das 2005, Reef & Lovelock 2015.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 86%
“…2a). Similarly, Ye et al (2005) found lower survival for Aegiceras corniculatum at 25 PSU, and Chen & Ye (2014) …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The average salinity levels were 13.72 dS m −1 , 19.57 dS m −1 , and 22.27 dS m −1 in Tubli, Sitra-1, and Sitra-2, respectively. In this context, it was reported that wastewater discharge had a positive effect on seedlings of mangroves through enhancement of growth and reducing the salt-induced damage to the physiological processes of plants [42].…”
Section: Community Structurementioning
confidence: 99%
“…Most of the deforestation is by local communities for using the mangrove logs for construction of their houses (huts) and as firewood, as our field enquiries revealed. At some locations, the bare ground appears in light (white to pale blue) tone (Figure 2-c) due to salt encrustation in the areas where the mangrove vegetation declined and the land dried out, because extreme salinity can lead the death of mangrove plants (Chen and Ye 2014). The main reason for increased salinity regime in certin parts of mangrove ecosystem is construction of dams and barrages across rivers and consequent reduction in freshwater inputs into the system through the rivers (Spalding et al 1997).…”
Section: Mangrove Degradation By Coastal Erosionmentioning
confidence: 99%